2020
DOI: 10.3389/fonc.2020.01472
|View full text |Cite
|
Sign up to set email alerts
|

Pros and Cons: High Proportion of Stromal Component Indicates Better Prognosis in Patients With Pancreatic Ductal Adenocarcinoma—A Research Based on the Evaluation of Whole-Mount Histological Slides

Abstract: The study aimed to investigate the potential of tumor–stroma ratio (TSR) on digitalized whole-mount histopathology to predict prognosis in patients with pancreatic ductal adenocarcinoma (PDAC). The effectiveness were evaluated through internal validation. Data were retrospectively collected from consecutive patients who underwent primary pancreatic resection from December 2016 to August 2017 (developing cohort) and from September 2017 to April 2018 (validation cohort). Digitalized whole-mount slide images were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…One recent multicenter retrospective study enrolling 778 PDAC patients who received surgical treatment between 2009 and 2014 showed that the rate of PNI was 87% among these patients (T0/1, 61.6%; T2, 86.7%; T3/4, 90.1%; N0, 72.5%; and N1, 93.0%) [ 102 ]. PNI was an independent risk factor for disease‐free survival (DFS) and/or OS ( P < 0.0001) [ 103 ], and could serve as a prognostic indicator [ 99 , 104 , 105 ]. Being PNI‐free was independently protective for long‐term survival (longer than 10 years) in PDAC patients [ 106 ].…”
Section: Clinical Significance Of Pnimentioning
confidence: 99%
“…One recent multicenter retrospective study enrolling 778 PDAC patients who received surgical treatment between 2009 and 2014 showed that the rate of PNI was 87% among these patients (T0/1, 61.6%; T2, 86.7%; T3/4, 90.1%; N0, 72.5%; and N1, 93.0%) [ 102 ]. PNI was an independent risk factor for disease‐free survival (DFS) and/or OS ( P < 0.0001) [ 103 ], and could serve as a prognostic indicator [ 99 , 104 , 105 ]. Being PNI‐free was independently protective for long‐term survival (longer than 10 years) in PDAC patients [ 106 ].…”
Section: Clinical Significance Of Pnimentioning
confidence: 99%
“…TSR was automatically calculated as the area of stroma divided by the area of the whole core (tumor and stroma). Compared with similar studies of computer aided-recognition methods [27][28][29], several technical improvements have been made in our study. Firstly, as mentioned above, the key for computerized TSR assessment is to identify the boundary of tumor nests more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…The statistics analysis was also refered to our previous research [13]. Categorical data are presented as percentages and were examined using the chi-squared test or Wilcoxon rank-sum test Univariate and multivariable Cox regression analyses were performed to identify independent prognostic factors, and hazard ratios (HRs) were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…We referred our previous research [13] 7) patients who did not complete 4 courses of S-1 administration. The therapy schedule was approved by the Institutional Review Board of Changhai Hospital and Hospital and all informed consent was obtained from participants or from the legally authorized representatives for participating in this study for chemotherapy for the start of oncological treatment, and the study was conducted in accordance with the Declaration of Helsinki and national guidelines.…”
Section: Cohort Developmentmentioning
confidence: 99%
See 1 more Smart Citation